2012
DOI: 10.1111/j.1539-6924.2012.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Are People Willing to Buy Natural Disaster Insurance in China? Risk Awareness, Insurance Acceptance, and Willingness to Pay

Abstract: After the Wenchuan earthquake (magnitude 7.9, May 12, 2008), intensive debates on how China should establish a natural disaster insurance system were initiated among researchers, policymakers, and insurance professionals. Our focus was the social aspects of disaster insurance, explored in China through a nationwide survey. Our questionnaires investigated people's risk awareness, insurance acceptance, their opinions on governmental measures for disaster management, and their willingness to pay for disaster hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 24 publications
9
55
0
6
Order By: Relevance
“…It appears that there is a relatively strong relationship between having been directly influenced by the earthquake and the purchasing of CEIP (Pearson χ 2 23.252 significance 0.000). This finding is in line with Wang et al's (2012) findings who found that an individual's previous earthquake experience plays an important role in the purchase of insurance policies. Of the people whose houses / flats had been damaged in previous earthquakes 57% of them purchased a CEIP.…”
Section: Findings Analysis and Discussionsupporting
confidence: 92%
“…It appears that there is a relatively strong relationship between having been directly influenced by the earthquake and the purchasing of CEIP (Pearson χ 2 23.252 significance 0.000). This finding is in line with Wang et al's (2012) findings who found that an individual's previous earthquake experience plays an important role in the purchase of insurance policies. Of the people whose houses / flats had been damaged in previous earthquakes 57% of them purchased a CEIP.…”
Section: Findings Analysis and Discussionsupporting
confidence: 92%
“…The relationship between disaster risk and per capita GDP as well as poverty in China also suggests that efforts to eliminate poverty and to increase development may be a successful policy implementation for effective disaster risk mitigation. Furthermore, there have less willingness to accept disaster insurance for people from regions with a greater multi-hazard threat, but buying insurance may be also an effective way to reduce disaster risk (Wang et al 2012c). In addition, the correlations between disaster risk and exposure as well as vulnerability demonstrate that risk was more closely related to exposure (R 2 = 0.94, p \ 0.01) than vulnerability (R 2 = 0.35, p \ 0.01) at the significance level of 0.01 (Fig.…”
Section: Chinese Disaster Risk Index (Cdri)mentioning
confidence: 99%
“…On the one hand, increasing levels of education could increase the ability to use risk management tools such as insurance (Vandeveer 2001;Sherrick et al 2004;Mishra and Goodwin 2006). Low levels of education may be associated with negative perceptions of insurance among farmers, thus lowering insurance uptake (Wang et al 2012). On the other hand, education can be used as a proxy variable for risk attitude (Sherrick et al 2004).…”
Section: H4: the Education Level Of The Household Head Is Positively mentioning
confidence: 99%